Measuring customer satisfaction towards HAI magazine amongst students at KPTM Bangi / Faizatul Fazliyana Jamaluddin - Jamaluddin, Faizatul Fazliyana (Faculty of Business and Management, 2010)
HAI, the acronym for Hiburan, Aksi & Informasi (entertainment, action, information), gives her reader’s entertainment news on the go. Utusan Karya Sdn Bhd and this magazine published HAI magazine on 3 August 1996. Nowadays, there are many competitors in the Malaysian magazine industry. Readers are given choices to choose their reading material for the magazine. Every month sale and circulation of HAI magazine become down. Many customers try to move to the other magazine. It can be prove based on research by Audit Bureau of Circulation, it state only 15,000 per month average circulation doing by HAI magazine in 2008-2009 Nowadays, business environment become dynamic and competitive, companies have put increased importance on measuring and also improving customer satisfaction. Following the scenario above, it is an alternative for researcher to study that focus on customer satisfaction on HAI magazine amongst students at KPTM Bangi. In this study, the population is students at KPTM Bangi and researcher distribute 317 questionnaires to respondents. From this study, researcher found that the most factors that influence customer satisfaction towards HAI magazine is front page and respondents are neither satisfied nor dissatisfied with HAI magazine.The researcher hopes that this research will provide some ideas, knowledge and awareness towards HAI magazine.